2019
DOI: 10.1093/brain/awz170
|View full text |Cite
|
Sign up to set email alerts
|

Parallel pathways of seizure generalization

Abstract: Generalized convulsive status epilepticus is a life-threatening emergency, because recurrent convulsions can cause death or injury. A common form of generalized convulsive status epilepticus is of focal onset. The neuronal circuits activated during seizure spread from the hippocampus, a frequent site of seizure origin, to the bilateral motor cortex, which mediates convulsive seizures, have not been delineated. Status epilepticus was initiated by electrical stimulation of the hippocampus. Neurons transiently ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
38
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 58 publications
5
38
0
1
Order By: Relevance
“…Though this is a limitation of this technique, the TRAP technique offers superior signal-to-noise ratio and time specificity compared to traditional cfos IHC, which has been shown in our work (Fig 8) and in previous work. 21,26 Also, it is important to point out that the absence of tdTomato expression does not necessarily mean the cell is not active. Induction of cfos response varies based on the frequency and strength of stimulus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though this is a limitation of this technique, the TRAP technique offers superior signal-to-noise ratio and time specificity compared to traditional cfos IHC, which has been shown in our work (Fig 8) and in previous work. 21,26 Also, it is important to point out that the absence of tdTomato expression does not necessarily mean the cell is not active. Induction of cfos response varies based on the frequency and strength of stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…21 Previous studies examined cfos immunohistochemistry (IHC) versus tdTomato-tagged cfos expression in the TRAP model, and found that TRAP has a superior signal-tonoise ratio and time specificity. 21,26 Validation in this experiment used cfos IHC 2 hours after HI. As a negative control, mice that did not receive 4-OHT were found to have no tdTomato expression.…”
Section: Trap Neuronal Activitymentioning
confidence: 99%
“…Neuronal plasticity mechanisms that facilitate the spread of seizures from the hippocampus to the motor cortex during generalized convulsive SE are not understood. Generalized convulsive seizures likely arise from the activation of neurons in the motor cortex . The hippocampus is a common site of origin of focal seizures, and it is injured during generalized convulsive SE in patients with complex febrile SE …”
mentioning
confidence: 99%
“…Generalized convulsive seizures likely arise from the activation of neurons in the motor cortex. 8,9 The hippocampus is a common site of origin of focal seizures, and it is injured during generalized convulsive SE in patients with complex febrile SE. 10,11 We hypothesized that α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor plasticity mediated by the GluA1 subunit is critical for secondary generalization of seizures and thus death during SE.…”
mentioning
confidence: 99%
“…Aún no se entienden bien los mecanismos que inician crisis anormalmente prolongadas (Sánchez Fernández, Goodkin, & Scott, 2019). Dabrowska y et al sugieren que la transmisión sostenida mediada por AMPAR (Receptor Alfa amino 3 hidroxil 5 metil 4 isoxacolepropiónico) y que las neuronas piramidales hipocampales tienen mayor reactivada durante crisis y EE (Dabrowska et al, 2019).…”
Section: Visión Desde El Modelo Diagnóstico 1: Definición De Ee a Parunclassified